1997
DOI: 10.1080/09540129750125307
|View full text |Cite
|
Sign up to set email alerts
|

Participatory evaluation of counselling, medical and social services of The AIDS Support Organization (TASO) in Uganda

Abstract: The AIDS Support Organization (TASO) is an indigenous non-governmental organization (NGO) of HIV-infected and affected people in Uganda. TASO provides counselling, social support, medical and nursing care for opportunistic infections at 7 centres affiliated to district hospitals in Uganda. Between 1993 and 1994, the services provided by TASO were evaluated through a participatory approach between staff and clients. TASO counselling services helped clients and their families to cope with HIV and AIDS, with 90.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…Kaleeba et al identified caretakers as mostly female, with 37% being farmers and 21% being unemployed. 1 This corresponds well with the findings of this survey, in which most active volunteers were women and had some form of regular income (e.g. their husbands were employed).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Kaleeba et al identified caretakers as mostly female, with 37% being farmers and 21% being unemployed. 1 This corresponds well with the findings of this survey, in which most active volunteers were women and had some form of regular income (e.g. their husbands were employed).…”
Section: Discussionsupporting
confidence: 60%
“…They found that 86% were female, 50% had seven years or more of education, 37% were farmers and 21% were unemployed. 1 Catherine Marenga described that volunteers in Zimbabwe are mostly experienced women who work in their own neighbourhoods. They were mostly involved in healthrelated volunteer work before starting to do Aids support.…”
Section: Introductionmentioning
confidence: 99%
“…The response to AIDS has in Uganda been characterised by openness and political support from all levels of government, and internationally recognised Ugandan NGOs have been key players in promoting the discourse of openness and in helping people to "live positively with AIDS". tASO (The AIDS Support Organisation), founded in 1987, is one of the best known of these (see for example Kaleeba et al 1997). Being able to join tASO has until recently been the most commonly mentioned reason for getting an hIv test done.…”
Section: Boundaries and Responsibilitiesmentioning
confidence: 99%
“…There was no intention to evaluate the education program itself; it has been described and evaluated elsewhere. 30,31 Rather, the intent was to learn about its relevance and impact from the perspective of those nurses who participated.…”
Section: Purposementioning
confidence: 99%